2009
DOI: 10.1590/s1414-49802009000200015
|View full text |Cite
|
Sign up to set email alerts
|

Género y trabajo: una intersección en construcción. Análisis de dos empresas recuperadas

Abstract: El presente artículo presenta las conclusiones de una investigación realizada en dos empresas recuperadas del área del Gran Rosario (Provincia de Santa Fe - Argentina). El objetivo fue comparar el proceso de lucha para recuperar las fuentes de trabajo que llevaron adelante un grupo de mujeres trabajadoras o esposas de trabajadores de cada empresa estudiada, constituyendo nuevos modelos de funcionamiento técnico y organizacional. La hipótesis de trabajo fue que para cada caso estudiado predominó una "lógica par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Although these pillars may not necessarily develop, and often tend to present vague and temporary boundaries, these multiple cleavages recurrently appear in the narration of conflicts and tensions within recuperated enterprises. For example, as several studies point out (Dicapua et al, 2011;Hudson, 2011;Rebón, 2007), interviewees of the analysed cases highlighted the repeated tension between workers that are deeply committed to the co-operative and undisciplined workers with a low level of commitment, often marked by the culture and practices of the salaried worker who is only interested in cashing the compensation.…”
Section: Recuperated Enterprises Express the Democratisation Of Produ...mentioning
confidence: 97%
“…Although these pillars may not necessarily develop, and often tend to present vague and temporary boundaries, these multiple cleavages recurrently appear in the narration of conflicts and tensions within recuperated enterprises. For example, as several studies point out (Dicapua et al, 2011;Hudson, 2011;Rebón, 2007), interviewees of the analysed cases highlighted the repeated tension between workers that are deeply committed to the co-operative and undisciplined workers with a low level of commitment, often marked by the culture and practices of the salaried worker who is only interested in cashing the compensation.…”
Section: Recuperated Enterprises Express the Democratisation Of Produ...mentioning
confidence: 97%
“…Esto permite ver la relación dialéctica entre necesidades y oportunidades, lo que sitúa estas realidades no previsibles en el plano de la invención, como una acción creativa de los/as trabajadores/as que permite superar las brechas entre el trabajo prescripto -y los hábitos adquiridos en el mismo -y los imprevistos del trabajo real. (Dicapua, Tavella y Valentino;2013).…”
Section: La Vinculación Inter-institucional Y El Aprendizaje Mutuounclassified
“…Similarly, the few studies that have examined gender in Argentine worker‐recovered businesses indicate that processes of organizational change open new opportunities for women. For example, case studies have found that women in worker‐recovered businesses have increased access to leadership positions (Monteagudo ), more control over their time (Fernández Álvarez and Partenio ), equal pay (Oseen forthcoming), and the ability to create new workplace gender identities (Dicapua, Perbellini, and Tifni ).…”
Section: Gender Inequalty In the Workplacementioning
confidence: 99%
“…Yet for both Paco and Carmen, these identities are active, empowered, and politically engaged (cf. Dicapua et al ).…”
Section: Gendering Processes In Hotel Bauenmentioning
confidence: 99%